The Effect Of Electronic Word Of Mouth And Customer Engagement On Purchase Intention Of Nike Products Using The Tiktok Brand Equity Application As A Moderator - Muhammad Rafi Padantya; Agus Abdurrahman (International Journal of Economics, Business and Innovation Research, 2024)
Companies are now competing in determining effective and efficient marketing strategies. Companies are required to keep up to date in marketing their products through various digital social media platforms which are currently mostly and are being used by companies to carry out product buying and selling activities. This study aims to analyze the effect of Electronic Word of Mouth and Customer Engagement on Purchase Intention of Nike Brand Equity Products as a Moderator. This study uses TikTok social media as a medium for marketing Nike products. This research was conducted using google forms and questionnaires distributed online. The research also requires 201 respondents, this research uses quantitative methods with data processing using PLS-SEM (smartpls). The results of this research test show that E-WoM has a positive effect on Brand Equity, E-WoM does not have a positive effect on Purchase Intention, Customer Engagement has a positive effect on Brand Equity, Customer Engagement has a positive effect on Purchase Intention, and Brand Equity has a positive effect on Purchase Intention.